THE EFFECT OF BOARD DIVERSITY AND MEETING FREQUENCY ON FINANCIAL PERFORMANCE OF CONSUMER NON-CYCLICAL COMPANIES - Haitsam, Muhammad Azzam; Jati, Handoyo; Leon, Farah Margaretha (Universitas Nusa Cendana, 2025)
In a quantitative analysis of panel data spanning 2020–2024 for consumer non‑cyclical firms on the Indonesia Stock Exchange, this research investigates how diversity in board demographics—namely age, tenure, and gender—and governance participation via meeting frequency affect firm profitability, as measured by Return on Assets and Return on Equity, while accounting for leverage and firm size. Results indicate that greater variation in directors’ professional experience significantly boosts ROA, whereas wider age disparities among board members negatively impact ROE, reflecting generational dynamics in decision‑making. In contrast, gender diversity and meeting frequency show no significant effects. The persistent influence of leverage and scale corroborates their vital role in financial performance. Altogether, the study demonstrates the value of diverse expertise and prudent financial management, highlighting that demographic effects are nuanced and context‑dependent in emerging‑market governance. Keywords: Board Diversity; Corporate Governance; Consumer Non-Cyclicals; Financial Performance